Lagovirus Non-structural Protein p23: A Putative Viroporin That Interacts With Heat Shock Proteins and Uses a Disulfide Bond for Dimerization - Smertina, Elena; Carroll, Adam J.; Boileau, Joseph; Emmott, Edward; Jenckel, Maria; Vohra, Harpreet; Rolland, Vivien; Hands, Philip; Hayashi, Junna; Neave, Matthew J.; Liu, Jian-Wei; Hall, Robyn N.; et al. (Frontiers in Microbiology, 2022)
The exact function(s) of the lagovirus non-structural protein p23 is unknown as robust cell culture systems for Rabbit haemorrhagic disease virus (RHDV) and other lagoviruses have not been established. Instead, a range of in vitro and in silico models have been used to study p23, revealing that p23 oligomerizes, accumulates in the cytoplasm, and possesses a conserved C-terminal region with two amphipathic helices. Furthermore, the positional homologs of p23 in other caliciviruses have been shown to possess viroporin activity. Here, we report on the mechanistic details of p23 oligomerization. Site-directed mutagenesis revealed the importance of an N-terminal cysteine for dimerization. Furthermore, we identified cellular interactors of p23 using stable isotope labelling with amino acids in cell culture (SILAC)-based proteomics; heat shock proteins Hsp70 and 110 interact with p23 in transfected cells, suggesting that they ‘chaperone’ p23 proteins before their integration into cellular membranes. We investigated changes to the global transcriptome and proteome that occurred in infected rabbit liver tissue and observed changes to the misfolded protein response, calcium signaling, and the regulation of the endoplasmic reticulum (ER) network. Finally, flow cytometry studies indicate elevated calcium concentrations in the cytoplasm of p23-transfected cells. Taken together, accumulating evidence suggests that p23 is a viroporin that forms Ca2+- conducting channels in the ER membranes.